PERAN ’URF SEBAGAI PENENTU HUKUM PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Syarif, Muhammad Isra; Misbahuddin, Misbahuddin; Lutfi, Mukhtar (Al-Maslahah : Jurnal Ilmu Syariah, 2024)
al-'Urf as a source of law has a role in social dynamics. al-'Urf can be used as a legal basis for certain conditions.  This research is qualitative research with the type of library research and uses a sociological normative approach method. The results of this research show that al-'Urf is what is considered good and right by humans in general and is done repeatedly so that it becomes a habit. al-'Urf is often equated with custom, but there is a difference, namely that the term custom only emphasizes the repetitive aspect of work, while al-'Urf only looks at the perpetrator. As for the similarities, adat and al-'Urf are work that has been accepted by common sense, embedded in the heart, carried out repeatedly and in accordance with the character of the perpetrator. al-‘Urf contributes to the flexibility of Islamic law and allows law to adapt to social changes without losing its fundamental values. This is in accordance with the fiqh rule "Al-'adah Muhakkamah" which means that customs can be the basis of law as long as they do not conflict with the Koran and hadith as well as the principles of justice.